2021
DOI: 10.5194/tc-2021-367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altimetric observation of wave attenuation through the Antarctic marginal ice zone using ICESat-2

Abstract: Abstract. The Antarctic marginal ice zone (MIZ) is a highly dynamic region where sea ice interacts with ocean surface waves generated in ice-free areas of the Southern Ocean. Improved large-scale (satellite-based) estimates of MIZ width and variability are crucial for understanding atmosphere-ice-ocean interactions and biological processes, and detection of change therein. Legacy methods for defining the MIZ width are typically based on sea ice concentration thresholds, and do not directly relate to the fundam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The provided algorithm has particular use when applied at scale. We expect 10 − 15% of the IS-2 tracks in polar regions to be dominated by waves (Brouwer et al, 2021). That implies roughly 3 − 4.5 × 10 3 cases of diverse wave observation in the MIZ (as of June 2022) to sample the large space of wave-ice interaction, which is likely enough to better constrain seaice wave interactions.…”
Section: Discussionmentioning
confidence: 97%
“…The provided algorithm has particular use when applied at scale. We expect 10 − 15% of the IS-2 tracks in polar regions to be dominated by waves (Brouwer et al, 2021). That implies roughly 3 − 4.5 × 10 3 cases of diverse wave observation in the MIZ (as of June 2022) to sample the large space of wave-ice interaction, which is likely enough to better constrain seaice wave interactions.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the properties of Antarctic ice cover do not directly depend on the degree of coverage. In-situ measurements carried out in the Southern Ocean showed that close pack ice with SIC up to 100% do have the dynamical properties of the MIZ (Alberello et al, 2019;Vichi et al, 2019;Brouwer et al, 2021), which discredits the reliability of thresholdbased definition. Vichi (2021) proposed an alternative MIZ definition that is based on statistical properties of the SIC and its spatial and temporal variability.…”
Section: Discussionmentioning
confidence: 99%
“…At any instant, the area of ice-covered regions with energetic ocean surface waves can be much smaller than that ‘influenced’ by waves more generally. In global measurements with the ICESat-2 altimeter, the MIZ was defined as those regions where waves were identified at least 7.5% of the time [ 6 ]—and of 4402 individual observations of sea ice heights in the Southern Ocean, just 304 (7.0%) were identified visually as having waves in them [ 15 ]. The MIZ is dynamic, and ICESat-2 overflights inconsistently sample the constantly varying sea ice surface.…”
Section: The Marginal Ice Zonementioning
confidence: 99%
“…The influence of ocean surface waves is also used to define the MIZ [10]. Waves can be observed propagating long distances within the sea ice [8,9,[11][12][13][14][15]. A companion review in this special issue discusses the theory and observation of waves in the MIZ [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation